Improvement of urban passenger ground transport structure based on coordinated development of subsystems - D. A. Dryuchin (Вестник СибАДИ, 2024)
Introduction. The high importance of the urban passenger transport complex as a system determining the level of socio-economic development of the urban area is formulated. One of the systemic problems of the passenger transport complex of modern cities is the decentralization of planning and management processes, which determines the structural imbalance of key subsystems. The results of a literary review are presented, during which the works devoted to improving the efficiency of the transport process, the process of providing energy resources and the process of maintaining rolling stock in good condition are considered. The necessity of developing a methodology ensuring the coordination of the state and functioning of key subsystems of the transport complex is noted. The purpose of scientific work is defined, the list of solved tasks is defined.Materials and methods. The structural scheme of the urban passenger transport complex is given, a conceptual approach to solving the problem of coordinated optimization of its key subsystems is described. The following are defined: the target indicator, the objective function and its limitations that determine the optimization process being implemented. A brief description of methods for determining and mutual coordination of structural parameters of subsystems forming the material basis of the transport complex is given.Results. Theoretical provisions reflecting a conceptual approach to ensuring the efficiency of urban transport systems based on the coordinated development of subsystems, based on the magnitude of the proposed integrated efficiency indicator, are presented. Based on the data obtained from the results of analytical studies and field experiments, a calculation was made that made it possible to determine the structural parameters of the subsystems of the urban passenger transport system of one of the cities, ensuring the maximum value of the efficiency of transport activities provided by structural coordination of the subsystems that make up the material basis of the urban passenger transport system.Discussion. The solution of the tasks set is reflected, indicators reflecting the achievement of the research goal are indicated, confirmation of the hypothesis about the possibility of improving the efficiency of the urban passenger transport complex through the implementation of conditions ensuring the coordinated development and interaction of key subsystems is formulated.Conclusion. A generalizing conclusion about the solution of an important scientific, methodological and applied task – to increase the efficiency of the passenger transportation process along urban passenger transport routes based on ensuring the coordinated development of the subsystems that make up its material base is formulated.